Observing cosmic microwave background polarization through ice - Pietranera, Luca; Buehler, Stefan A.; Calisse, Paolo Gherardo; Emde, Claudia; Hayton, Darren John; John, Viju Oommen; Maffei, Bruno; Piccirillo, Lucio; Pisano, Giampaolo; Savini, Giorgio; Sreerekha, T. R. (Monthly Notices of the Royal Astronomical Society, 2007)
Ice crystal clouds in the upper troposphere can generate polarization signals at the μK level. This signal can seriously affect very sensitive ground-based searches for E and B modes of cosmic microwave background polarization. In this paper, we estimate this effect within the CℓOVER experiment observing bands (97, 150 and 220 GHz) for the selected observing site (Llano de Chajnantor, Atacama desert, Chile). The results show that the polarization signal from the clouds can be of the order of or even bigger than the cosmic microwave background expected polarization. Climatological data suggest that this signal is fairly constant over the whole year in Antarctica. On the other hand, the stronger seasonal variability in Atacama allows for a 50 per cent of clean observations during the dry season.